Staffing Up and Dropping Out - Fetler, Mark (Education Policy Analysis Archives, 1997)
Growing public school enrollment and the need to maintain or improve service to students has increased the demand for teachers, perhaps more rapidly than existing sources can accommodate. While some schools recruit well qualified teachers by offering higher salaries or better working conditions, others may satisfy their need for staff by relaxing hiring standards or assigning novice teachers to difficult classrooms. Schools' hiring policies have consequences for student success. Dropout rates tend to be higher where faculties include a greater percentage of minimally educated teachers or teachers with little experience. The relationship between dropout rate and teacher qualifications is independent of student poverty, school size, and location. A proposed strategy to reduce dropout rates is to encourage higher preparation and employment standards, and to provide appropriate classroom assignments, mentoring, and support for new teachers.